Fahr’s Syndrome: A Typical Entity Presenting as Psychosis - Kumar, Prerak; Kukreti, Prerna; Saurabh; Mathur, Harita; Kohat, Komal; Kataria, Dinesh (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2020)
Fahr’s syndrome is a rare neurological entity characterized by bilateral and symmetrical intracranial deposition of calcium mainly in the basal ganglia. Motor and Psychiatric symptoms are clinically relevant features in this syndrome. We report a case where psychiatric symptoms and features of delirium were more prominent as compared to motor symptoms. Radiological findings depicted bilateral basal ganglia calcification and oedema in parietal region mainly on right side. Parathyroid hormone and calcium levels were mildly low with no significant past or family history. Most behavioural symptoms showed significant improvement on treatment with Risperidone, Amisulpride, Lorazepam, Sodium Valproate, Calcium, Folic acid and Trihexyphenidyl but some symptoms like auditory hallucinations remained unresponsive. How to cite this article: Kumar P, Kukreti P, Mathur H, Saurabh, Kohat K, Kataria D. Fahr’s Syndrome: A Typical Entity Presenting as Psychosis. J Adv Res Psychol Psychother 2020; 3(1): 29-31. DOI: https://doi.org/10.24321/2581.5822.202006